2016
DOI: 10.56890/jpacd.v18i.57
|View full text |Cite
|
Sign up to set email alerts
|

Production and trends of scientific research on cactus pear in mainstream journals

Abstract: To identify production and trends on publications of cactus pear from 1900 to 2015 at aninternational level, a review of qualitatively and quantitatively indexed bibliographicrecords from Science Citation Index Expanded (SCIE) and Social Sciences Citation Index(SCIE) was conducted. The analyses included the concepts or key words ‘opuntia’ as wellas the common names of cactus pear and its variants. It was found that there were 1,472documents regarding cactus pear, from which 50% were published during the last t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
1
2
1
Order By: Relevance
“…The results in Table 3 show that the pH value of prickly pear pulp was 6.07. The pH value of prickly pear pulp obtained in this study was within the range reported by Reis et al (2018) in Portuguese prickly pear fruit varieties (6.03-6.47) and by El-Samahy et al (2006) and El-Samahy et al (2009) in yellow prickly pear pulp (6.00-6.14). It is similar to those reported by Mohammed et al (2014) for the pH in prickly pear fruits, which were 6.02.…”
Section: Ph Value and Titratable Aciditysupporting
confidence: 88%
See 3 more Smart Citations
“…The results in Table 3 show that the pH value of prickly pear pulp was 6.07. The pH value of prickly pear pulp obtained in this study was within the range reported by Reis et al (2018) in Portuguese prickly pear fruit varieties (6.03-6.47) and by El-Samahy et al (2006) and El-Samahy et al (2009) in yellow prickly pear pulp (6.00-6.14). It is similar to those reported by Mohammed et al (2014) for the pH in prickly pear fruits, which were 6.02.…”
Section: Ph Value and Titratable Aciditysupporting
confidence: 88%
“…It is also less than the value discovered by Bourhia et al (2020) for Moroccan prickly pear pulp varieties, which ranged from 281.98 to 582.91 in the 2015 and 2016 seasons, respectively. It is also lower than the results of El-Samahy et al (2009) for red prickly pear pulp, which was 224.07. These differences could be caused by differences in the stage of maturity, the environment, and the genotype of prickly pears.…”
Section: °Brix/acidity Ratiocontrasting
confidence: 63%
See 2 more Smart Citations